Composite membrane of polyguanidine cationic surface for desalination. Issue 5 (22nd March 2022) - Han, Qingfeng; Liu, Dongqing; Huang, Xiaohua; Xie, Qinxing; Meng, Jianqiang
Abstract: Surface positve-charged composite membranes were prepared through two guanidine group containing polymers, polyhexamethylene guanidine (PHMG) and polyhexamethylene biguanidine (PHMB). They were used as aqueous phase monomers in an interfacial polymerization (IP) process reacting with trimesoyl chloride (TMC) on the surface of polysulfone (Psf) ultrafiltration membrane. Piperazine (PIP) provided the best pH adjustment among the chosen regulators. As guanidine groups dissociate in water and bring ammonium cations to membrane surfaces, both polyguanidine endowed membranes reacted with divalent metal cations better compared with Na + and Li + . The rejection rates were more than 90% for all chosen divalent metal salts. PHMG membranes displayed excellent enrichment of Li + from a mixed solution of Mg 2+ and Li + salts. The Mg 2+ /Li + mass ratio decreased from 60 to 3.7, accompanying a −3.6% rejection to Li + . Although partial guanidine groups participated in the IP reaction, bactericidal rates of membranes were both higher than 99% in Gram-negative E. coli and Gram-positive S. aureus tests. HIGHLIGHTS: Removal of harmful heavy metal ions. Multiple metal ion removal. Excellent separation of magnesium and lithium. Nanofiltration membrane against microbial contamination. Cation surface nanofiltration membrane. Graphical Abstract